Analisis Bauran Pemasaran Pada UMKM Kuliner - Sir Kalifatullah Ermaya (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2022)
The existence of culinary SMEs as the center of economic activity for most Indonesian people has begun to be displaced by the modern market. Therefore, improving service quality is important in increasing consumer loyalty in order to maintain it. Researchers conducted research with qualitative methods and used descriptive statistics to determine the 7P's marketing mix at